Effectiveness of Computer-Generated Virtual Reality (VR) in Learning and Teaching Environments with Spatial Frameworks - Parviz Safadel; David White (Applied Sciences, 2020)
In this paper, we highlight the benefits of using computer-generated VR in teaching instructional content that have spatial frameworks such as in science, technology, engineering, and mathematics (STEM) courses. Spatial ability scores were collected from a sample (N = 62) of undergraduate and graduate students. Students were required to complete an instructional tutorial in VR and computer desktop screening on DNA molecules, which included necessary information about DNA and nucleotide molecules. Students also completed a comprehensive test about the spatial structure of DNA and a feedback questionnaire. Results from the questionnaire showed media use and satisfaction to be significantly related. The results also showed a significant interaction between spatial ability levels (low, medium, and high) and media used on students’ spatial understanding of the DNA molecules. It may be concluded that VR visualization had a positive compensating impact on students with low spatial ability.